Examining innovation as process: Action research in journalism studies. (April 2019) - Wagemans, Andrea; Witschge, Tamara
In this article, we discuss how 'action research' as an experiential research approach allows us to address challenges encountered in researching a converged and digital media landscape. We draw on our experiences as researchers, co-developers and marketeers in the European Union-funded Innovation Action project 'INnovative Journalism: Enhanced Creativity Tools' (INJECT) aimed at developing a technological tool for journalism. In this media innovation process, as in other media practices, longstanding delineations no longer hold, due to converging professional disciplines and blurring roles of users and producers. First, we discuss four features of innovation in the current 'digital' media landscape that come with specific methodological requirements: (a) the iterative nature of innovation; (b) converged practices, professions and roles; (c) the dispersed geographic nature of media production and innovation processes and (d) the impact of human and non-human actors. We suggest action research as a possible answer to these requirements of the digital media landscape. Drawing on our experiences in the INJECT project, we illustrate how adopting an action research approach provides insight into the non-linear, iterative and converged character of innovation processes by highlighting: (a) how innovation happens at various moments, in various places and by various people; (b) how perceptions and enactments of professions change over time and (c) how roles are (re)combined and expanded in such a way that clear delineation is not easy. Ultimately, we argue that experiencing convergence through action research enables us to do justice to the complexity of the current media landscape.